2000
DOI: 10.3935/rsp.v7i1.267
|View full text |Cite
|
Sign up to set email alerts
|

Potrebe starijih osoba za cjelovitim uslugama skrbi u lokalnoj zajednici

Abstract: Izvorni znanstveni članak UDK: 364.6 (053.9) Primljeno: veljača 2000. U članku su prikazani prvi rezultati istraživanja kojemu je cilj razviti modele otvorene skrbi za starije ljude, primjerene suvremenom pristupu socijalne skrbi za starije u Europi, a usklađene s tradicionalnim i drugim obilježjima starijeg pučanstva u Hrvatskoj. Prikazana su osnovna sociodemografska obilježja ispitanih starijih osoba, njihovo obiteljsko i zdravstveno stanje te dostupnost različitih zdravstvenih, socijalnih i drugih usluga, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
2
0
2
Order By: Relevance
“…This categorization provided valuable insights into the potential impact of one's living situation on their health beliefs. Remarkably, these findings are consistent with a 2000 study (39) that identified similar living arrangements among retirees in the region, and they align with other relevant studies (41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 92%
“…This categorization provided valuable insights into the potential impact of one's living situation on their health beliefs. Remarkably, these findings are consistent with a 2000 study (39) that identified similar living arrangements among retirees in the region, and they align with other relevant studies (41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 92%
“…There are certain differences in the sense that a larger number of respondents in urban areas wash their clothes completely by themselves (56:54%), while, in rural areas, all the laundry has to be done by other people (28:14%). In the study by Havelka et al, it was estimated that 25-30% of the elderly need the help of another person or a caregiver to do their laundry (14). Toplek, in her research, concludes that most of the respondents (28.1%) participate in washing the laundry, while 10.9% of the respondents do not participate and need the help of other people (15).…”
Section: Discussionmentioning
confidence: 99%
“…Također, mnogi empirijski dokazi sugeriraju da je socijalna podrška vrlo značajna u starijoj dobi te može biti jedna od važnih prednosti produljenja života. Istraživanje koje je provedeno u Republici Hrvatskoj pokazuje da su vrsta i količina socijalne podrške kao i veličina socijalne mreže vrlo važne odrednice kvalitete i dužine života (Havelka, 2000.). Despot Lučanin (2008.)…”
Section: Raspravaunclassified